2016
DOI: 10.1002/jnr.23992
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure to enriched environment rescues chronic stress‐induced impaired hippocampal synaptic plasticity, anxiety, and memory deficits

Abstract: Exposure to prolonged stress results in structural and functional alterations in the hippocampus including reduced long-term potentiation (LTP), neurogenesis, spatial learning and working memory impairments, and enhanced anxiety-like behavior. On the other hand, enriched environment (EE) has beneficial effects on hippocampal structure and function, such as improved memory, increased hippocampal neurogenesis, and progressive synaptic plasticity. It is unclear whether exposure to short-term EE for 10 days can ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 75 publications
9
48
1
1
Order By: Relevance
“…A large body of evidence demonstrated chronic stress-induced neuronal remodeling in limbic structures such as the hippocampus 3 - 6 , 26 , 27 . Specifically, the diminished synaptic efficacy of hippocampal CA1 neurons was suggested to be related to abnormal structural plasticity which results in failure to consolidate long-term memory 12 , 13 . The postsynaptic architecture of excitatory synapses is regarded as an important component of connectivity between neurons, ultimately modulating neuronal excitability 13 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence demonstrated chronic stress-induced neuronal remodeling in limbic structures such as the hippocampus 3 - 6 , 26 , 27 . Specifically, the diminished synaptic efficacy of hippocampal CA1 neurons was suggested to be related to abnormal structural plasticity which results in failure to consolidate long-term memory 12 , 13 . The postsynaptic architecture of excitatory synapses is regarded as an important component of connectivity between neurons, ultimately modulating neuronal excitability 13 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding behavioral effects, some studies in rats submitted to chronic stress have shown that EE improved working memory performance in the T-maze task, and prevented anxiety-like behavior in the elevated plus maze test (Bhagya et al, 2017). EE also prevented depression-like behavior in the sucrose preference test, and partially prevented the anxiogenic-like effect of chronic stress, attenuating the spatial learning difficulty and memory impairment in the radial arm maze in rodents (Shilpa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to impaired spatial memory, enhanced fear memory and impaired extinction, aged WT mice also showed increased anxiety and depressive-like behaviors 6 months after midlife stress, consistent with the persistent behavioral abnormalities associated with stress-related psychopathologies ( Finsterwald and Alberini, 2014 ). Whereas increased anxiety and depressive-like behaviors have been reported days after chronic stress in rats and mice ( Bhagya et al, 2017 ; Santana et al, 2015 ), few studies have examined affective behaviors months after stress. Increased anxiety-related behaviors have been reported in rats 3 months after predator stress ( Zoladz et al, 2015 ) but until now the persistence of depressive-like behaviors months after stress cessation has not been described.…”
Section: Discussionmentioning
confidence: 99%